Intellectualibus propositionibus to Gulin and Erdogan toward the Religion and state - Alwan , Assistant lecturer Muntaha Hassaan (The International and Political Journal, 2023)
The Islamic experience in Turkey has re-emerged strongly after declining for several decades due to exclusionary secularism. This experience blended Islam and modernity, and it was able to achieve successes at all levels, but it quickly split in 2016 after an alliance through which it was able to reach power. Due to the importance of this experience, this research seeks to present the intellectual proposals of Fethullah Gulen and Recep Tayyip Erdogan because of their resonance and impact on Turkish reality. These proposals were not deeply different because they both focused on the necessity of reforming the individual and the state, and each of them had a different point of view. They also both criticized the strict secularism that the Kemalists believed in as a philosophy for religion and the state. These philosophical proposals did not contribute to the events of the dispute, but rather other controversial issues emerged that contributed to the escalation of the dispute between them.